Scandcleft randomised trials of primary surgery for unilateral cleft lip and palate: 7. Occlusion in 5 year-olds according to the Huddart and Bodenham index. Issue 1 (2nd January 2017) - Karsten, Agneta; Marcusson, Agneta; Hurmerinta, Kirsti; Heliövaara, Arja; Küseler, Annelise; Skaare, Pål; Bellardie, Haydn; Rønning, Elisabeth; Shaw, William; Mølsted, Kirsten; Sæle, Paul; Brinck, Eli; et al.
Abstract: Background and aim: Good dentofacial development and good occlusion are main goals in the treatment of UCLP. The aim was to evaluate dental occlusion at age 5 years with the Huddart and Bodenham index after four different protocols of primary surgery for UCLP. Design: Three parallel randomised controlled trials were undertaken as an international multicentre study by 10 cleft teams in five countries: Denmark, Finland, Sweden, Norway, and the UK. Methods: Three different surgical procedures for primary palatal repair (Arms B, C, and D) were tested against a common procedure (Arm A) in the total cohort of 448 children born with non-syndromic UCLP. Dental casts of 418 patients (272 boys, 146 girls), at the mean age of 5.1 years (range =4.7–6.9) were blindly assessed by 10 orthodontists with the original Huddart and Bodenham index. The main outcome measure was dental occlusion. Results: The inter- and intra-examiner reliability was good-to-excellent (0.61–0.94; 0.66–1.0, respectively). The mean total scores (+2 to −18) varied from −5.56 (Trial 2C) to −7.21 (Trial 3D). The mean anterior scores (+2 to −6) varied from −1.66 (Trial 2C) to −2.56 (Trial 3A). The mean posterior cleft-side scores (0 to −6) varied from −3.24 (Trial 3A) to −3.82 (Trial 3D) and the mean non-cleft-side scores (0 to −6) varied from −0.60 (Trial 2C) to −1.30 (Trial 3A); however, no significant differences were found within the trials. Conclusion: There was no statistical evidence of a difference in occlusion between the two surgical methods in each trial. Trial registration: ISRCTN29932826.